Penegakan Hukum dalam Penanganan Konflik Pelanggaran Hak Asasi Manusia di Papua - Labibah Iqbal, Asyaima; Rasyaad Akmal, Athaya; El Hakam Hilmy, Muhammad; Deni, Fitra (JURNAL KAJIAN ISLAM MODERN, 2024)
This study explores the significant decline in the human rights situation in Papua since 2018, marked by increased conflict and human rights violations by security forces. The research aims to understand the complexity of this phenomenon and identify potential solutions. A qualitative method was used, with descriptive data from previous studies, human rights reports, and official documents. The findings indicate that the conflict has led to killings, enforced disappearances, and torture, with existing law enforcement efforts proving unsatisfactory. The discussion reveals that the conflict also impacts education, health, and natural resource management, exacerbating poverty and hindering sustainable development. The study concludes that legal reform and a more sensitive approach to the local context are necessary to address human rights issues in Papua, as well as the importance of sustainable development that considers environmental conservation and the welfare of the local community. The government has taken significant steps to improve health infrastructure and access to services. Still, a more substantial commitment is needed to ensure the fulfillment of the fundamental rights of the Papuan people